2022
DOI: 10.1029/2021gl097547
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Look at the Temperature Gradient Contribution to the Dayside Magnetopause Current

Abstract: The magnetopause is a magnetosphere boundary layer created through the dynamic pressure balance between the solar wind's kinetic pressure and Earth's magnetic field. The solar wind causes distortions in the magnetosphere's magnetic field topology supported by a current sheet first proposed by Chapman and Ferraro (1931), often termed the Chapman-Ferraro (CF) current, which runs in a dawn-to-dusk direction around the magnetopause (Ganushkina et al., 2018). This current structure is believed to be generated throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…This is especially useful for computing higher resolution single-spacecraft measurements of quantities such as the electron pressure divergence ∇ ⋅ P e within electron-scale structures smaller than the spacecraft separation, which is commonly the case for thin current sheets and EDRs at the magnetopause. Using these single-spacecraft measurements, we found that the perpendicular contribution to ∇ ⋅ P e was three to four times larger than previously reported (Shuster et al, 2019), which affects our understanding of the force balance of terms in the electron momentum equation and generalized Ohm's law (e.g., Beedle et al, 2022). Additionally, we showed single-spacecraft measurements of 𝐴𝐴 (∇ ⋅ 𝐏𝐏𝑒𝑒) ∕∕ that exhibit better agreement with the extended regions of enhanced parallel electric field E // similar to the EDR event first reported by Wilder et al (2017) within the magnetosheath, and consistent with 3D particle-in-cell (PIC) simulations (Liu et al, 2013).…”
Section: Conclusion Discussion and Outlookmentioning
confidence: 62%
“…This is especially useful for computing higher resolution single-spacecraft measurements of quantities such as the electron pressure divergence ∇ ⋅ P e within electron-scale structures smaller than the spacecraft separation, which is commonly the case for thin current sheets and EDRs at the magnetopause. Using these single-spacecraft measurements, we found that the perpendicular contribution to ∇ ⋅ P e was three to four times larger than previously reported (Shuster et al, 2019), which affects our understanding of the force balance of terms in the electron momentum equation and generalized Ohm's law (e.g., Beedle et al, 2022). Additionally, we showed single-spacecraft measurements of 𝐴𝐴 (∇ ⋅ 𝐏𝐏𝑒𝑒) ∕∕ that exhibit better agreement with the extended regions of enhanced parallel electric field E // similar to the EDR event first reported by Wilder et al (2017) within the magnetosheath, and consistent with 3D particle-in-cell (PIC) simulations (Liu et al, 2013).…”
Section: Conclusion Discussion and Outlookmentioning
confidence: 62%
“…This method was applied to both the EDR and regular crossings, with the results for the average current density for the 225 regular events matching within error the average current over the magnetopause crossing times identified by the Paschmann et al (2018) database's minimum variance analysis method as previously reported in J. M. H. Beedle et al (2022). The performance of our algorithm was also manually checked over the 26 EDR events so that the selected magnetopause crossing correctly captured the EDR event as previously identified by their respective papers.…”
Section: Magnetopause Identificationmentioning
confidence: 85%
“…The most prevalent of these is regarding the increased presence of parallel current in EDR events. Not only is this parallel current stronger than in the regular magnetopause, but also represents an interesting counterpoint to the primarily perpendicular, ion dominated diamagnetic current seen in the background magnetopause current sheet (e.g., J. M. H. Beedle et al (2022)). As the inner EDR is void of appreciable magnetic field components in the 𝐴𝐴 M𝑀 or 𝐴𝐴 φ𝜙 direction (for low to no guide field cases), this 𝐴𝐴 φ𝜙 parallel current indicates that a measurable and significant current in this direction is detected inside the outer IDR, becoming parallel to its 𝐴𝐴 M𝑀 directed Hall magnetic field.…”
Section: Current Structure In Edr Eventsmentioning
confidence: 99%
See 2 more Smart Citations